Hepatic inflammation elicits production of proinflammatory netrin‐1 through exclusive activation of translation. Issue 5 (1st April 2022) - Barnault, Romain; Verzeroli, Claire; Fournier, Carole; Michelet, Maud; Redavid, Anna Rita; Chicherova, Ievgeniia; Plissonnier, Marie‐Laure; Adrait, Annie; Khomich, Olga; Chapus, Fleur; Richaud, Mathieu; Hervieu, Maëva; et al.
Abstract: Background and Aims: Netrin‐1 displays protumoral properties, though the pathological contexts and processes involved in its induction remain understudied. The liver is a major model of inflammation‐associated cancer development, leading to HCC. Approach and Results: A panel of cell biology and biochemistry approaches (reverse transcription quantitative polymerase chain reaction, reporter assays, run‐on, polysome fractionation, cross linking immunoprecipitation, filter binding assay, subcellular fractionation, western blotting, immunoprecipitation, stable isotope labeling by amino acids in cell culture) on in vitro–grown primary hepatocytes, human liver cell lines, mouse samples and clinical samples was used. We identify netrin‐1 as a hepatic inflammation‐inducible factor and decipher its mode of activation through an exhaustive eliminative approach. We show that netrin‐1 up‐regulation relies on a hitherto unknown mode of induction, namely its exclusive translational activation. This process includes the transfer of NTN1 (netrin‐1) mRNA to the endoplasmic reticulum and the direct interaction between the Staufen‐1 protein and this transcript as well as netrin‐1 mobilization from its cell‐bound form. Finally, we explore the impact of a phase 2 clinical trial‐tested humanized anti‐netrin‐1 antibody (NP137) in two distinct, toll‐like receptor (TLR) 2/TLR3/TLR6‐dependent, hepatic inflammatory mouse settings. We observe a clear anti‐inflammatory activity indicating the proinflammatory impact of netrin‐1 on several chemokines and Ly6C+ macrophages. Conclusions: These results identify netrin‐1 as an inflammation‐inducible factor in the liver through an atypical mechanism as well as its contribution to hepatic inflammation. Abstract :